Measurement of a magnonic crystal at millikelvin temperatures - Kosen, S; Morris, R; van Loo, A; Karenowska, A (American Institute of Physics, 2018)
Hybrid systems combining magnons and superconducting quantum circuits have attracted increasing interest in recent years. Magnonic crystals (MCs) are one of the building blocks of room-temperature magnonics and can be used to create devices with an engineered band structure. These devices, exhibiting tunable frequency selectivity and the ability to store travelling excitations in the microwave regime, may form the basis of a set of tools to be used in the context of quantum information processing. In order to ascertain the feasibility of such plans, MCs must be demonstrated to work at the low temperatures required for microwave-frequency quantum experiments. We report the measurements of the transmission of microwave signals through an MC at 20 mK and observe a magnonic bandgap in both continuous-wave and pulsed excitation experiments. The spin-wave damping at low temperatures in our yttrium iron garnet MC is higher than expected, indicating that further work is necessary before the full potential of quantum experiments using magnonic crystals can be realised.